Day 1 Panel 4: Fixing What's Broken: Reforming the System - William C. Silverman; Christine Perumal; Karla George; Joan Gerhardt; Denise Kronstadt (Columbia Journal of Gender and Law, 2023)
Day 1 – October 13, 2022 Keynote Panel 4: Fixing What's Broken: Reforming the System